Gut microbiome directs hepatocytes to recruit MDSCs and promote cholangiocarcinoma - Zhang, Qianfei; Ma, Chi; Duan, Yi; Heinrich, Bernd; Rosato, Umberto; Diggs, Laurence P.; Ma, Lichun; Roy, Soumen; Fu, Qiong; Brown, Zachary J.; Wabitsch, Simon; Thovarai, Vishal; et al. (Cancer discovery, 2021)
Gut dysbiosis is commonly observed in patients with cirrhosis and chronic gastrointestinal disorders; however, its effect on antitumor immunity in the liver is largely unknown. Here we studied how the gut microbiome affects antitumor immunity in cholangiocarcinoma. Primary sclerosing cholangitis (PSC) or colitis, two known risk factors for cholangiocarcinoma which promote tumor development in mice, caused an accumulation of CXCR2+ polymorphonuclear myeloid-derived suppressor cells (PMN-MDSC). A decrease in gut barrier function observed in mice with PSC and colitis allowed gut-derived bacteria and lipopolysaccharide to appear in the liver and induced CXCL1 expression in hepatocytes through a TLR4-dependent mechanism and an accumulation of CXCR2+ PMN-MDSCs. In contrast, neomycin treatment blocked CXCL1 expression and PMN-MDSC accumulation and inhibited tumor growth even in the absence of liver disease or colitis. Our study demonstrates that the gut microbiome controls hepatocytes to form an immunosuppressive environment by increasing PMN-MDSCs to promote liver cancer.MDSCs have been shown to be induced by tumors and suppress antitumor immunity. Here we show that the gut microbiome can control accumulation of MDSCs in the liver in the context of a benign liver disease or colitis.See related commentary by Chagani and Kwong, p. 1014.This article is highlighted in the In This Issue feature, p. 995
Gesehen am 22.02.2022